Використання Figma для розробки адаптивного дизайну веб-сайтів - Івченко, В. Р. (ХНУРЕ, 2024)
This work investigates responsive web design in Figma, detailing its historical context, essential elements, and the creation of adaptive layouts. It underscores the Breakpoints plugin's significance in improving designers' productivity and work quality, exploring its functionality in setting breakpoints and automatically generating frames for different screen sizes. Additionally, it presents a practical example of using the plugin to design a real layout, illustrating its effectiveness in adapting websites for various devices and showcasing its practical application in the design process.
Keywords: використання Figma; дизайн веб-сайтів